Long-term outcomes in high-bleeding risk patients undergoing PCI for acute coronary syndromes: results from a large single-center pci registry. (25th November 2020) - Nicolas, J; Cao, D; Claessen, B; Sartori, S; Chandiramani, R; Roumeliotis, A; Goel, R; Camaj, A; Beerkens, F; Turfah, A; Dangas, G; Baber, U; et al.
Abstract: Introduction: Current clinical guidelines recommend prolonged dual antiplatelet therapy (DAPT) following percutaneous coronary intervention (PCI) in patients presenting with acute coronary syndromes (ACS). However, an extended DAPT duration in high-bleeding risk (HBR) patients amplifies the risk of post procedural complications. Hence, clinicians often face the dilemma of prolonging DAPT duration to prevent recurrent ischaemic events at the expense of increasing the incidence of bleeding in high-risk patients. The actual incidence of ischaemic and bleeding events in this particular population is not well elucidated. Purpose: To evaluate one-year ischemic and bleeding outcomes following PCI for ACS in a real-world HBR population as defined by the Academic Research Consortium (ARC) consensus document. Methods: We included all patients who presented with ACS to a high-volume single PCI centre from 2012 to 2017 and underwent PCI with 2nd generation drug-eluting stent implantation. Patients were classified as HBR if they met ≥1 major or ≥2 minor criteria according to the recent ARC-HBR consensus. The outcomes of interest were major adverse cardiovascular events (MACE), a composite of all-cause death, myocardial infarction (MI), and target lesion revascularization (TLR), and major bleeding events, including both peri-procedural and post-discharge bleeding. All outcomes were assessed at 1-year follow-up. The Kaplan-Meier method was used for time-to-event analyses. Results: Out of 6, 097 ACS patients included in this analysis, 2, 717 (44.6%) fulfilled the ARC-HBR definition. Compared to non-HBR group, HBR patients were more frequently female, older, more likely to have cardiovascular risk factors (e.g., diabetes, hypertension, and hyperlipidemia) and complex coronary artery disease (e.g., multi-vessel disease, bifurcation lesions, and calcification). The 1-year incidence of MACE was significantly higher in HBR patients (16.3% vs. 8.1%, HR 2.16, 95% CI [1.81–2.59], p<0.001) (Figure 1A). This finding was driven by higher rates of all-cause death and MI (Figure 1B). The 1-year incidence of major bleeding was also significantly higher in HBR patients compared to non-HBR (11.1% vs. 3.1%, HR: 3.92, 95% CI 3.10–4.95; p<0.001). Conclusions: HBR patients undergoing PCI for ACS are not only subject to bleeding complications but are also at an increased risk for ischemic events and all-cause mortality. Funding Acknowledgement: Type of funding source: None